ANALISIS PEMBELAJARAN KEWIRAUSAHAAN PADA MAHASISWA D3 PERBANKAN SYARIAH DALAM MEMBANGUN ENTREPRENEURIAL INTENTIONSEBAGAI PENCAPAIAN THE YOUNG ENTREPRENEUR - Fiandi, Mufti (Islamic Economics Program, Faculty of Islamic Economics and Business, 2018)
Entrepreneurship is believed to be an important force in global economic growth that creates new business and economic growth, and as one solution to the problem of unemployment. While entrepreneurship learning is an important component of business education has been shown to provide stimulus for individual in making or considering entrepreneurship as a career choice that enhances the creation of new businesses and economic growth. Entrepreneurship learning in higher education should ideally be implemented in the long term, through a gradual process of learning and development. This study aims to see how the influence of entrepreneurial learning in building entrepreneurial intentions to be the young entrepreneur. The study was conducted with a sample of 100 respondents from Faculty of Economics and Islamic Business majoring Diploma 3 sharia banking students at UIN Raden Fatah. The survey was conducted with questioner during May – July 2017. Data were processed using Structural Equation Model (SEM). The result showed that entrepreneurship learning positive affect the entrepreneurial intention. Entrepreneurship learning has positive influence on the young entrepreneur. There is a greater direct influence of entrepreneurship learning to the young entrepreneur than indirect effect through entrepreneurial intention. Entrepreneurial intention positive affect the young entrepreneur.